Indeks Penulis Volume 27, Tahun 2007 - Indeks Penulis Volume 27, Tahun 2007 (agriTECH, 2007)
Anwar, C. 112Arif, S.S. 59Astuti, M. 7, 112Aulanni’am. 100Basuki, R. 59Eriyathi, N. I. 41Gardjito, M. 89Haryadi. 18Hintono, A. 7Hustiany, R. 118Jatmiko, M. W. 48Lestari, A. S. P. 33Maksum, M. 33Marseno, D. W. 18Masithoh, R. E. 48Maspanger, D. R. 124Murtiningrum. 48, 59Pambayun, R. 89Pujimulyani, D. 70Purwadaria, H. K. 75Purwantana, B. 130Purwanto, M. Y. J. 95Rahardjo, B. 18, 27Rahayu, E. S. 7Rahayu, K. 89Ratnaningsih. 27Riyanto, S. 107Rohman, A. 107Rusman. 1Setyawan, N. 137Subagio, A. 100Sudarmadji, S. 89Sudyastuti, T. 137Suhargo. 27Supriyadi. 112Supriyanto. 18Suroso. 75Suryanto, E. 1Sutrisno. 75Syaefullah, E. 75Tiven, N.C. 1Wariyah, C. 112Widjanarko, S. B. 100Widodo, K. H. 33, 41Witono, Y. 100Wuryastuti, H. 7Yuliana, N. 12, 82